Secondary school students' motivation to participate in environmental conservation volunteer program - Wong, Li Juan (2021)
The environmental conservation volunteer program provides secondary school students the opportunity to connect to their environment and contribute to its natural heritage conservation. However, there is a lack of school students participating in environmental conservation volunteer programs. This is because they perceived these programs to be irrelevant to them as most times the programs cater to volunteers who are adults and senior citizens. Hence, many existing environmental conservation volunteer program is ill-fitting to school students’ motivation. A qualitative research was conducted to explore the motivation of secondary school students who had volunteered in an Environmental Conservation Volunteer Program (ECVP) in the state of Perak. Data was primarily gathered using focus group discussions to provide exploratory and descriptive findings of school students’ motivation, opportunity and ability to volunteer in the ECVP. The focus group discussion was conducted at the end of the study, using questions developed based on the Motivation- Opportunity-Ability (MOA) theoretical framework. The group discussions involved forty-five secondary school students who had participated actively in the program. All discussions were audio-recorded and analyzed thematically using a constant comparative method and critical incident analysis to identify recurring themes across the dataset. The observation was used to triangulate findings from the group discussions. Seven themes emerged from the analysis to describe secondary school students’ intrinsic and extrinsic motivation to participate in the ECVP. The intrinsic motivation were gain new experiences and knowledge, seeking altruistic value, personal enhancement, and the love of nature, while the extrinsic motivation were the influences of social norms and goal-orientation. The study identified the barriers and facilitators to describe the situational conditions that influenced students’ actual volunteering participation and their continuous involvement in the program. Social factors, transportation and duration of the program have been identified as the barriers to their continued participation in the program. The desire to receive certificate, parents’ approval, good mentors and instructors, activities which fit their interest and food are the facilitators which enhanced their motivation to participate in the program. The implementation process of the ECVP that is cyclical and repetitive had enhanced their ability to perform the tasks, which encouraged their actual participation and continuos involvement in the program. The volunteering experiences also offer various benefits to the volunteers as they ride through the volunteering program's challenges and learning experiences. Understanding secondary school student’s motivation enables an organization to design an ECVP that is in line with their motivation to encourage their actual participation. The barriers and facilitators identified to school students’ participation would also help organizations take important measures to increase students’ actual participation and continuous involvement in the ECVP and ensure students gained benefits from their participation.